(untitled) (International Journal of Language, Literacy and Translation, 2026)
The rise of digital communication has reshaped language learning, with internet memes emerging as a compellingmedium for linguistic and cultural engagement. Far beyond humorous images, memes are multimodal texts thatconvey layered meanings and reflect contemporary social discourse. This study explores how memes function as bothresources and challenges for intermediate Korean language learners: on one hand, memes provide exposure tocolloquial expressions, slang, and cultural references from digital spaces such as social media applications, K-popfandoms and other online communities, while on the other hand, their visual complexity and culturally specificcontent can hinder comprehension, revealing gaps in learners’ sociocultural awareness. Using a qualitative casestudy design, this research analyzes learners’ interactions with Korean memes, mostly their interpretation,discussion, and creation. This research investigates how university Korean language learners engage theirsocial/digital media usage with their linguistic development and intercultural competence. The study highlights theneed for deeper empirical inquiry into how learners process and respond to meme-based content, suggesting thatmemes hold valuable pedagogical potential when integrated thoughtfully into language education.Keywords: Korean language learning, internet memes, intercultural competence, digital literacy, languageacquisition